Nilai Religius Pada Novel Kubah Karya Ahmad Tohari: Tinjauan Sosiologi Sastra Dan Implementasinya Sebagai Bahan Pembelajaran Sastra Di SMA N 2 Sukoharjo - Aisah, Aisah; , Drs. Adyana Sunanda, M.Pd (2016)
The purpose of this study is (1) describe the structure of the Kubah novel by Ahmad Tohari (2) describe the religious values in it and (3) describe the implementation of the results of the analysis of religious values of the novel as literay materials in high school. The type of reseach is qualitative descriptive research, and reseach design with content analysis. The object of this reseach is the word and sentences which containing a message of religious values in the Kubah novel, through the approach of sociologi of literature. Data collection techniques used in the reseach is the literature, read, observe, and record, with interview. The validity of the using triangulasi theory. Data analysis techniques used in this research is the technique of dialectic. The results of analysis can be summed up as follows. First, based on the structural analysis, the novel's theme is religius values. The main character named Karman and additional figuree, i.e. Haji Bakir, Rifah, Tini, Jabir, Marni, Parta, Captain Somad, Khastagethek, Margo, Triman, and Si Gigi Baja. The flow of the story is declined flow (regressive). The setting is divided into three part: the pleace setting located in Maluku Utara, and Pegaten. The time setting orcuredd berween 1948-1977. Social bacground tell the life of the people were friendly and easy to forgive others. Second, the religious values in the Kubah novel by Ahmad Tohari comprise faith, syariah (worship and muamalah), and morals. Playload confidence to god in the Kubah novel by Ahmad Tohari in the back Karman belive the existense of god. Third, the results of the analysis of religious values in the Kubah novel by Ahmad Tohari are implemented as literary materials in high school based on core competence and basic competences class XII on the 3.1 i.e. understanding the structure and rules of narative text history, news, advertising, editorial/opinion, and novel orally and in the writing. 4.1 interpretating the meaning of the text of historical stories, news, advertising, editorial/opinion, and novel orally and in the writing.